Hormone‐substrate changes with exenatide plus dapagliflozin versus each drug alone: The randomized, active‐controlled DURATION‐8 study. Issue 1 (8th October 2019) - Ferrannini, Ele; Baldi, Simona; Frías, Juan P.; Guja, Cristian; Hardy, Elise; Repetto, Enrico; Jabbour, Serge A.; DeFronzo, Ralph A.
Abstract: Aim: To determine the effects of individual and combined therapies on plasma insulin, glucagon, β‐hydroxybutyrate (β‐OH) and associated metabolites. Materials and Methods: In DURATION‐8, the combination of once‐weekly exenatide (EQW) + 10 mg dapagliflozin (Dapa) in patients with type 2 diabetes poorly controlled with metformin‐reduced HbA1c levels and body weight (at weeks 28 and 52) was compared with EQW + placebo (Plb) or Dapa + Plb. The study included 678 patients randomized 1:1:1 to EQW + Dapa, EQW + Plb, or Dapa + Plb. Plasma insulin and glucagon were measured at fasting and 2 hours after a mixed meal. Fasting plasma free fatty acids (FFA) and β‐OH concentrations were measured. Results: The fasting insulin‐to‐glucagon molar ratio (I/Glg) increased with EQW + Plb only; postprandial I/Glg increased in all groups but significantly more with EQW + Plb. β‐OH, FFA, and glycerol concentrations showed a parallel response: larger increments with Dapa + Plb, larger decrements with EQW + Plb, and intermediate changes with EQW + Dapa. β‐OH levels and I/Glg were inversely related to one another. Patients in the top quartile of β‐OH changes from baseline [median (interquartile range): +207 (305) vs. −65 (−154) μmol/L; P  < .0001] were more frequently treated with Dapa + Plb, had higher urine glucose‐to‐creatinine ratios, and lower fasting insulin [52 (51) vs. 68 (53) pmol/L; P = .0013) and I/Glg [1.76 (1.49) vs. 2.23 (1.70) mol/mol; P = .0020]. Haematocrit increased only in the Dapa group. Conclusions: The EQW + Dapa combination abolished the Dapa‐induced rise in β‐OH, reduced the EQW‐induced increase in I/Glg, maintained glycosuria, and increased haematocrit in patients with poorly controlled type 2 diabetes. The drug combination may preserve any putative benefits while mitigating the risk of ketoacidosis.